2017
DOI: 10.1016/j.colsurfa.2017.05.071
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired fog capture and channel mechanism based on the arid climate plant Salsola crassa

Abstract: q¤ ursoyD wF nd rrrisD wFF nd howningD tFyF nd frrientosElomoD FxF nd grlettoD eF nd prkD eFiF nd urmnD wF nd fdylD tFFF @PHIUA 9fioinspired fog pture nd hnnel mehnism sed on the rid limte plnt lsol rssF9D golloids nd surfes e X physiohemil nd engineering spetsFD SPW F ppF IWSEPHPF

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 28 publications
0
24
0
2
Order By: Relevance
“…The thicknesses of both polymers on the Si surface is around 200 nm. In the literature, iCVD of PPFDA has been widely studied, and it was revealed that the long perfluoroalkyl groups of PFDA has natural tendencies to reorient themselves to form large crystalline structures . This can be the most probable reason behind the observation of increased surface roughness for PPFDA films.…”
Section: Resultsmentioning
confidence: 99%
“…The thicknesses of both polymers on the Si surface is around 200 nm. In the literature, iCVD of PPFDA has been widely studied, and it was revealed that the long perfluoroalkyl groups of PFDA has natural tendencies to reorient themselves to form large crystalline structures . This can be the most probable reason behind the observation of increased surface roughness for PPFDA films.…”
Section: Resultsmentioning
confidence: 99%
“…There are several studies conducted to compare the efficiency of both methods for a specific application [ 14 , 15 ]. In this work, we intend to employ both methods to functionalize the PU foam surfaces and compare the resultant modified foams, particularly for the oil absorption process.…”
Section: Introductionmentioning
confidence: 99%
“…Fluoropolymer thin films are one of the most commonly used hydrophobic coatings 48–52 . However, the effect of fluorochemicals on human health and the environment is increasingly recognized as a serious, worldwide concern 53 .…”
Section: Resultsmentioning
confidence: 99%
“…Fluoropolymer thin films are one of the most commonly used hydrophobic coatings. [48][49][50][51][52] However, the effect of fluorochemicals on human health and the environment is increasingly recognized as a serious, worldwide concern. 53 Based on the wettability results of PECVD PI thin film in this study, PI thin film can be considered as a promising alternative to fluoropolymers.…”
Section: Film Structuresmentioning
confidence: 99%